Low temperature and surfactant-free synthesis of Pd2Sn intermetallic nanoparticles for ethanol electro-oxidation. (1st December 2016) - Wang, Congmin; Wu, Yurong; Wang, Xin; Zou, Liangliang; Zou, Zhiqing; Yang, Hui
Abstract: Many intermetallic compounds have a predictable structure, interesting electronic effects, and useful catalytic properties. In this work, a low temperature, surfactant-free, and one-pot method is used to synthesize carbon supported Pd2 Sn intermetallic nanoparticles. The superlattice of the product was then characterized using X-ray diffraction and transmission electron microscopy. These synthesized intermetallic nanoparticles were found to exhibit a higher activity and stability for electrocatalysis of the ethanol oxidation reaction in an alkaline media than has been achieved using a traditional Pd/C catalyst, which could be attributed to the structural and compositional stabilities of ordered Pd2 Sn intermetallic nanoparticles.